Groundwater Flow Modeling in the Malioboro, Yogyakarta, Indonesia - Alwan Satapona; Doni Prakasa Eka Putra; Heru Hendrayana (Journal of Applied Geology, 2018)
Malioboro is a famous tourism area in Yogyakarta City, in which there aremany hotels and increases every years and this follows by the increasing needs of fresh water taken from underlying groundwater. The decreasing of groundwater table become a great issue on this area, therefore the objective of the research is to predict groundwater table change in the next 10 years due to increase abstraction of groundwater. To answer the mentioned objectives, field observation of dug wells and collection of secondary data of log bores also calculation of recharge and water abstraction are used to understand and build the conceptual model of local groundwater system. The prediction is done by conducting simulation on a numerical groundwater model by using MODFLOW. The local groundwater system consists of two aquifer layers; upper aquifer and lower aquifer which separated incompletely by clay layer. Simulation is conducting by distributing the groundwater pumping for domestic and non-domestic utilization by dug wells in the upper aquifer, whereas deep wells non-domestic utilization are applied only in the lower aquifer. Simulations are conducted twice for the recent day and the next ten years predictionof groundwater abstraction. In the case of groundwater abstraction in the next tenyears, dug wells abstraction and deep wells pumping are setting to 4727 m3/day and 1648 m3/day, respectively. The groundwater pumping rates is representing increase of groundwater withdrawal of users in the range only between 0.2–1.2 % per year compare to the recent condition. The simulation reveals change occur on groundwater table depth and pattern. In average, the groundwater table will decrease of about 0.25 meter.